Estado del arte de métodos de gestión de residuos de llantas usadas en Colombia (2017)
Resolution 1457, from Environment Ministry, in 2010, created the waste tire management system, in paper. But, nowadays, problem continues: uncontrolled accumulation, atmospheric and visual pollution, plagues and diseases proliferation. In this context, was made a literature review on the alternatives applied in Colombia. This study is the first step for future researches.